The human and the physical in Debussy’s depictions of snow - Oravitz, Michael (Les Cahiers de la Société québécoise de recherche en musique, 2013)
This article explores Debussy’s musical engagement of the topic of snow in two representative works for piano, “Des pas sur la neige” from Préludes, Book I and “The Snow is Dancing” from Children’s Corner. In the analysis of “Des pas,” a narrative is put forth based on the interpretation of the work’s opening short-long rhythmic figure as a representation of contact with a frozen, encrusted surface followed by an immediate collapse of that frozen surface and contact with the ground underneath. As the work’s protagonist engages in walking meditation to confront a troubling memory, a state of contemplation is achieved whereby the musical portrayal of the footsteps are momentarily suppressed in strategic portions of the work designed to portray recollection, as Steven Rings (2008) has noted. In my analysis, I argue that the closing measures’ portrayal of footsteps is shifted into binary alterations of two notes, D and G, in steady quarter notes, so as to illustrate the protagonist’s emergence from an off beaten path to a more trodden one. In “The Snow is Dancing,” Debussy shifts focus from that of human emotion to the actual physical properties of snow. Interestingly, the snow is anthropomorphized nonetheless into dancers. I trace shifts in rhythm, line and register, and engage gestures of motion to illustrate Debussy’s compositional approach to both gravitationally suspending and animating wind-driven snowflakes.